Cultural Capital of a community to adapt in prone areas with floods, land subsidence and its Architectural representation. Case Study in Bandarharjo Semarang - Ameir, Muchi Juma; Ekomadyo, Agus S; Hutomo, Cahyo Septianto (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2020)
Most of the community in Northen part of Semarang especial in Kampung Bandarharjo that is 1.5km distance to Kota Lama Semarang they are surrounded by Kali Semarng and the Kali baru that is has been the reason of flash flooding disaster and (rob) tidal flood from seawater, currently they are still live in prone areas to disasters such as tidal floods and land subsidence, they have their own ways to adapt and survive into their context relating with what type of disaster they face and what mitigation culture they have so as to adapt with the built environment. This means of survival could be interpreted as indigenous knowledge that has been transferred in many generations and represents people’s lifestyle. The methods they used for culture mitigation can be also interpreted in architectural form based on their local understanding and their surrounding environment, it comprises on skills, credentials, manners and knowledge. These terms will rely on the Cultural Capital from Forms of Capital by Pierre Boudier Concept. These skills while they have improved can be utilized in other areas of the same context and same structure of community.  Indigenous knowledge, as a local knowledge has been gathered and passed through generations of living in a specific location, belongs to and is sustained by communities. Indigenous knowledge also involves of thoughts, experiences, practices and material that have been created locally or produced elsewhere, but have been transformed by local people and incorporated into the local way of life. DOI: https://doi.org/10.26905/lw.v12i1.3704